2019
DOI: 10.1525/collabra.200
|View full text |Cite
|
Sign up to set email alerts
|

Neither Cue Familiarity nor Semantic Cues Increase the Likelihood of Repeating a Tip-of-the-Tongue State

Abstract: Psycholinguistic and metacognition researchers mostly disagree on what constitutes a tip-of-the-tongue (TOT) state. Psycholinguists argue that TOT states occur when there is a transmission of activation failure between the lemma and phonology levels of word production (e.g., Burke, MacKay, Worthley, & Wade, 1991). Metacognition researchers argue that the TOT state is better described as a subjective experience caused by a mechanism that assesses the likelihood of recall from memory. One sub-hypothesis of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…There is a significant effect of context word familiarity, with participants being less likely to experience TOP and amnesia if a character is embedded in a more familiar two-character word than a less familiar one. Such effect is consistent with the observation that cue familiarity enhances the feeling of knowing judgements (Schwartz & Metcalfe, 1992), and more importantly, consistent with the finding in character amnesia (Huang et al, in press), though it is inconsistent with the finding that, in a test–retest TOT task, cue familiarity between the two tests does not produce an effect (Oliver et al, 2019). In addition, such effect is also consistent with the observation that context helps to facilitate the spoken and handwritten production (Jescheniak et al, 2017; Shao & Rommers, 2020; R.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There is a significant effect of context word familiarity, with participants being less likely to experience TOP and amnesia if a character is embedded in a more familiar two-character word than a less familiar one. Such effect is consistent with the observation that cue familiarity enhances the feeling of knowing judgements (Schwartz & Metcalfe, 1992), and more importantly, consistent with the finding in character amnesia (Huang et al, in press), though it is inconsistent with the finding that, in a test–retest TOT task, cue familiarity between the two tests does not produce an effect (Oliver et al, 2019). In addition, such effect is also consistent with the observation that context helps to facilitate the spoken and handwritten production (Jescheniak et al, 2017; Shao & Rommers, 2020; R.…”
Section: Discussionsupporting
confidence: 82%
“…Findings regarding semantic effects on word form retrieval have been mixed. Oliver et al (2019) observed that additional semantic cues do not help to reduce TOT states. Based on this finding, they argued that speakers have full access to semantic representations in a TOT state but fail to retrieve the full word form as a result of broken links between lemma and phonology.…”
Section: Discussionmentioning
confidence: 95%
“…The metacognitive account of the TOT phenomenon (Schwartz, 1999(Schwartz, , 2002Schwartz and Metcalfe, 2011) has been challenged. In contrast to earlier work (Metcalfe et al, 1993;Schwartz, 2010), subsequent studies failed to support the view that TOT states may be caused by cue familiarity or cue-induced emotional arousal (D'Angelo and Humphreys, 2012;Oliver et al, 2019). Before considering group recall as a retrieval-independent TOTinducing factor, making a stringent, "double dissociation" case would be advisable.…”
Section: Functional Dissociationsmentioning
confidence: 86%